Early Postharvest Time Period Affects Quality of Butterhead Lettuce Packed in Crates - Agüero, Maria Victoria (2012)
The period between when butterhead lettuce (Lactuca sativa var. L) heads are harvested and are stored in cold rooms can be upto 24 hrs. During this period, environmental conditions are uncontrolled, and the heads could undergo deterioration that has not been previously quantified. Quality changes of lettuce heads packed in crates, and exposed to optimal or sub-optimal conditions, during the 24 hrs after harvest were evaluated. Effects of placement within the crate (lower, middle and upper layer) were assessed. Proximity of heads within crates created a barrier to transfer of heat and humidity. This resulted in negative responses for plants under optimal conditions, because there was a delay in temperature reduction and there was deterioration in quality. At sub-optimal conditions the response was positive because respiration and transpiration allowed development of a saturated environment around heads delaying quality loss. This effect was most obvious in heads from middle and lower layers which present the highest overall visual quality and water content. Use of crates caused high mechanical damage on produce, and it was necessaary to discard outer leaves leading to weight losses of 10 and 35% for optimal and sub-optimal conditions, respectively. Initial quality rapidly decreases in the first day after harvest. It is necessary that technologies be upgraded to reduce quality and economic losses.